Linguistic Structure for Simile in Abdul- Kaher Al-Jerjani A Theoretical Study - Bouthaina souliman (دراسات في اللغة العربيّة وآدابها)
This study provides a reading in simile from its linguistic structural point of view in Abdul- Kader Al-Jerjani, showing its linguistic elements when the "compose a special kind of writing", and form a specified linguistic rhythm, that leads it to wholeness of writing, in linking between the grammatical and rhetoric. The study discussed the pictorial imagery with inditing , with the form of its linguistic structure, so it was found that it performs special functions, such as: It identifies the limits between a rhetoric form and another, especially metaphor, that is in the scope of the similar, and it identifies the type of simile it distinguish between one form and another, and from it in simile is discovered the same complicated kind that is spread on a wide aligning space. After that the research with Abdul Kaher studied the most important elements of building simile, its linguistic and semantic secrets with a focus on "the simizlied" and "simile tool".